2022
DOI: 10.1108/pr-02-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive leadership and knowledge sharing in Japanese workplaces: the role of diversity in the biological sex of workplace personnel

Abstract: PurposeThis study aims to examine the impact of managers’ inclusive leadership (IL) on knowledge-sharing (KS) behavior. Additionally, the authors consider the cross-level moderation effect of diversity in the biological sex of employees on the relationship between IL and employee KS behaviors.Design/methodology/approachA two-wave questionnaire survey was conducted in a large Japanese company. The sample included 827 employees (254 men and 573 women) in 129 groups. The authors, then, conducted a cross-level ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Our study revealed the positive effects of paradoxical leadership in fostering work engagement ultimately leading to individual performance outcomes in terms of job performance, innovative work behavior and voice behavior. Our multilevel research design also benefits the performance literature by providing a more fine-grained, supervisor–subordinate interface perspective which is limited in the current literature (Morinaga et al. , 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed the positive effects of paradoxical leadership in fostering work engagement ultimately leading to individual performance outcomes in terms of job performance, innovative work behavior and voice behavior. Our multilevel research design also benefits the performance literature by providing a more fine-grained, supervisor–subordinate interface perspective which is limited in the current literature (Morinaga et al. , 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In particular, by examining how paradoxical leadership would increase employees’ work engagement, and in turn foster employees’ in-role (job performance) and extra-role (innovative work behavior and voice behavior) performance outcomes, we contribute to the work engagement literature, since the majority of existing studies have focused on individual-level antecedents of work engagement, and work engagement and performance (both in-role and extra-role performance) have not been examined together with organizational-level paradoxical leadership. In particular, Morinaga et al. (2022) encouraged more research on the multilevel, antecedent-focused research on work engagement.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The theoretical lens of innovation reveals among determinants of innovation such as mission, goals and strategy, leadership, structures and systems, organizational learning, knowledge management and organizational culture (Crossan and Apaydin, 2010; Mendoza-Silva, 2021), emerging-market firms need to focus on the roles of leadership and knowledge resources to foster frugal innovation (Le et al , 2022; Iqbal and Piwowar-Sulej, 2023). Especially, inclusive leadership (IL) is considered as one of the preeminent leadership styles that have a considerable influence on knowledge sharing (KS) behaviors (Morinaga et al , 2022), thereby driving innovation capability of organizations (Gong et al , 2021; Gui et al , 2022). Although IL and KS are considered as prerequisite factors for innovation, limited empirical research has been directed toward the impact of IL and KS behaviors on specific form of innovation (Vladić et al , 2021; Gong et al , 2021; Morinaga et al , 2022) such as frugal innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, inclusive leadership (IL) is considered as one of the preeminent leadership styles that have a considerable influence on knowledge sharing (KS) behaviors (Morinaga et al , 2022), thereby driving innovation capability of organizations (Gong et al , 2021; Gui et al , 2022). Although IL and KS are considered as prerequisite factors for innovation, limited empirical research has been directed toward the impact of IL and KS behaviors on specific form of innovation (Vladić et al , 2021; Gong et al , 2021; Morinaga et al , 2022) such as frugal innovation. As a result, this study is produced to fill these theoretical gaps and advance the understanding of pathway leading to frugal innovation in emerging countries by following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the relationship between inclusive leaders and their followers is likely to be influenced by social exchanges (Choi et al, 2015;Korkmaz et al, 2022;Morinaga et al, 2023). Previous studies on inclusion and inclusive leadership have utilised the social exchange theory (SET) to examine the impact of inclusion and its importance for individuals, groups and organisations (Shore et al, 2011;Xiaotao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%